2011
DOI: 10.1007/s10803-011-1320-z
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Repetitive, Self-Injurious and Aggressive Behavior in Children With Severe Intellectual Disability

Abstract: We evaluated the independent association between adaptive behavior, communication and repetitive or ritualistic behaviors and self-injury, aggression and destructive behavior to identify potential early risk markers for challenging behaviors. Data were collected for 943 children (4-18 years, M = 10.88) with severe intellectual disabilities. Odds ratio analyses revealed that these characteristics generated risk indices ranging from 2 to 31 for the presence and severity of challenging behaviors. Logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 44 publications
3
80
1
3
Order By: Relevance
“…Matson's review (2009) showed that, until recently, little work has been done on the development of aggression among infants and toddlers at risk for IDD, although it is often linked with risk factors for SIB and abnormal stereotyped behaviors in older children and adults with IDD (Matson, Cooper, Malone, & Moskow, 2008; Matson, Dixon & Matson, 2005; McClintock, Hall, & Oliver, 2003; Oliver, Petty, Ruddick, & Bacarese-Hamilton, 2012). Most of these studies indicate a higher frequency of aggression, SIB, stereotypy, and hyperactivity, tantrums, and so forth, especially more among children with autism spectrum disorders (ASD) and IDD than among those with language delay or typical development.…”
mentioning
confidence: 99%
“…Matson's review (2009) showed that, until recently, little work has been done on the development of aggression among infants and toddlers at risk for IDD, although it is often linked with risk factors for SIB and abnormal stereotyped behaviors in older children and adults with IDD (Matson, Cooper, Malone, & Moskow, 2008; Matson, Dixon & Matson, 2005; McClintock, Hall, & Oliver, 2003; Oliver, Petty, Ruddick, & Bacarese-Hamilton, 2012). Most of these studies indicate a higher frequency of aggression, SIB, stereotypy, and hyperactivity, tantrums, and so forth, especially more among children with autism spectrum disorders (ASD) and IDD than among those with language delay or typical development.…”
mentioning
confidence: 99%
“…Another explanation may be that the increased demands of the academic environment may interfere with the performance of RRSBI, leading to an aggressive attempt to escape academic tasks (i.e., operant model, Reese, Richman, Belmont, & Morse, 2005; Reese, Richman, Zarcone, & Zarcone Reese, 2003; White et al, 2011). Additionally, the academic setting may place greater burden on the individual’s behavioral regulation system leading to higher rates of RRSBI and aggression (i.e., neuropsychological model; Oliver, Petty, Ruddick, & Bacarese-Hamilton, 2012; Turner, 1997). Clinical experience also suggests that anxiety and mood may play a role in the relationship of these factors as irritability, frustration, and stress may escalate in the absence of RRSBI (which may serve as a coping strategy), leading to an aggressive reaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, a key clinical symptom that has been noted among individuals with ID and comorbid mood disorders is self-injury and/or suicidal behaviors. Self-injury has been known to occur among individuals with ID (40 %), and with higher likelihood among those with severe ID and/or co-occurring ASD (Hill and Furniss 2006;Holden and Gitlesen 2006;Oliver et al 2012). It is important to make the distinction that the function of self-injury is different for individuals with ID in comparison to typically developing children.…”
Section: Other Comorbiditiesmentioning
confidence: 99%
“…It has also been observed that individuals with ID are more likely to engage in problem behaviors such as aggression and self-injury due to more severe ID symptomology (Kurtz et al 2011;Kurtz et al 2003). The prevalence rate of self-injury among children with severe ID is around 17-30 % (MacLean et al 2010;Oliver et al 2012). Among youth with ID from ages 13-17, the prevalence rates for suicidal ideation are 22-60 %, while suicidal behaviors range from 17-48 % (Ludi et al 2012).…”
Section: Other Comorbiditiesmentioning
confidence: 99%